The Religious Perfectionism Scale: A Cross-cultural Psychometric Evaluation Among Christians in the United States - Wang, Kenneth T. (Journal of psychology and theology, 2023)
The Religious Perfectionism Scale (RPS) was first developed among Chinese Buddhists, Christians, and Muslims. It consists of the following two subscales: Zealous Religious Dedication and Religious Self-Criticism. In this study, a cross-cultural psychometric evaluation of RPS was performed in a US Christian sample (N = 233). The confirmatory factor analysis (CFA) results presented a strong data-to-model fit statistics for the two-factor oblique model (CFI = .977, SRMR = .051, RMSEA = .034) in the US sample. The measurement of invariance between US and Chinese samples was examined by multiple-group CFA. The results indicated that the RPS fulfilled invariance for factor loadings and residual variances, but intercepts were partially invariant. The internal consistency reliability coefficients for the two subscales were adequate (above .70). The construct validity test results confirmed our hypotheses that the ZRD was positively correlated with Religious Commitment (r = .56), and the RSC was positively correlated with Scrupulosity (r = .58). Overall results suggest that the RPS is a promising measure of religious perfectionism for Christians in the United States. The implications of this were discussed.